Development of a Forehand Drive Table Tennis Training Model for Juvenile Offenders at the Special Juvenile Rehabilitation Institution in Bengkulu - Andriyani, Mas'ullah; Nopiyanto, Yahya Eko; Rizky, Oddie Barnanda; Sugihartono, Tono; Raibowo, Septian (Indonesian Journal of Sport, Health and Physical Education Science, 2024)
This research aims to develop a forehand drive training model in table tennis, specifically designed for juvenile inmates at the Bengkulu Special Penitentiary for Children. This research uses a Research and Development (R&D) approach, using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The method used is the descriptive qualitative method. The study population consisted of juvenile inmates in correctional institutions, with a simple random sampling technique. Research instruments include observation, interviews, questionnaires, and documentation. The validation results from experts showed a high level of approval: material experts at 94%, language experts at 90%, and media experts at 92%. The small group trial involving 10 juvenile inmates resulted in an average approval rating of 86%, while the large group trial with 30 participants resulted in an average approval rating of 90%. Based on these findings, it can be concluded that the Table Tennis Forehand Drive Training Model developed for juvenile inmates at the Bengkulu Special Penitentiary for Children is "Highly Feasible" to be implemented as a new training model at the institution.